2016
DOI: 10.1039/c5ra25546e
|View full text |Cite
|
Sign up to set email alerts
|

Study on the preparation of PAM/MMT W/W emulsion and its application as a flocculant

Abstract: OMMT was first prepared by intercalation of AM into MMT, then the OMMT was added into the dispersion polymerization system of polyacrylamide/montmorillonite water in water (WPAMt) emulsion and gelatin was used as the stabilizer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…26,27 Recently, as a promising intermediate in developing novel halogen-free ame retardants, 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide (DOPO) have been frequently used to synthesize effective and efficient phosphaphenanthrene-containing ame retardant additives for various polymer materials. [28][29][30][31][32][33] And some similar works have also suggested that the addition of phosphaphenanthrenecontaining additive indeed improved the ame retardancy of PC materials effectively. 34 Hence, the research on the phosphaphenanthrene-containing compound ame retarding PC materials is worth further exploring and investigating.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Recently, as a promising intermediate in developing novel halogen-free ame retardants, 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide (DOPO) have been frequently used to synthesize effective and efficient phosphaphenanthrene-containing ame retardant additives for various polymer materials. [28][29][30][31][32][33] And some similar works have also suggested that the addition of phosphaphenanthrenecontaining additive indeed improved the ame retardancy of PC materials effectively. 34 Hence, the research on the phosphaphenanthrene-containing compound ame retarding PC materials is worth further exploring and investigating.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, gelatin has been widely and successfully applied in the wastewater process as a basic material but not as a stabilizer . In our previous study, gelatin was used to prepare a PAM W/W emulsion in an ammonium sulfate–water system. Because of the negative influence from inorganic salt, it is of great significance to prepare PAM with only gelatin as the stabilizer through a polymer–water system.…”
Section: Introductionmentioning
confidence: 99%